'Data sheet of nanocomposites with F/N-doped ZnO' - Chen, Shuyang; Skordos, Alexandros A.; Kumar Thakur, Vijay (Cranfield University, 2024)
The dataset for this research comprises the measurement results for pristine PVDF and PVDF-ZnO nanocomposites with and without fluorine/nitrogen doping. For TGA, DSC and XRD results each file contains the relevant data per experimental technique. Within each file worksheets correspond to the different materials. The column headers specify the variables and their associated units. For dielectric tests, the data is organised in separate files for permittivity, loss and imaginary modulus. The data are organised in worksheets by material in 2D arrays. The rows correspond to spectra at different measured temperatures and the columns to fixed frequency data. The materials nomenclature is as follows: -PVDF: pure PVDF -PVDF+5% ZnO: PVDF with 5% ZnO by weight -PVDF+10% ZnO: PVDF with 10% ZnO by weight -PVDF+15% ZnO: PVDF with 15% ZnO by weight -PVDF+5% F-ZnO: PVDF with 5% Fluorine doped (10% molar fraction) ZnO by weight -PVDF+10% F-ZnO: PVDF with 10% Fluorine doped (10% molar fraction) ZnO by weight -PVDF+15% F-ZnO: PVDF with 15% Fluorine doped (10% molar fraction) ZnO by weight -PVDF+5% N-ZnO: PVDF with 5% Nitrogen doped (10% molar fraction) ZnO by weight-PVDF+10% N-ZnO: PVDF with 10% Nitrogen doped (10% molar fraction) ZnO by weight -PVDF+15% N-ZnO: PVDF with 15% Nitrogen doped (10% molar fraction) ZnO by weight
Keywords: 'Polymer-ceramic particle composites'; 'Dielectric spectroscopy'; 'Relaxation'; 'Dielectric storage'; 'Thermal analysis'